Promosi Penjualan dan Kualitas Layanan pada Minat Beli Ulang Cafe D’nada Bangkalan - Zehroh, Halimatus; Purnomo, Hadi (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
Based on the existing phenomena and problems, this study aims to determine the effect of sales promotion and service quality on repurchasing intention of Cafe D'nada Bangkalan. The method used in this research is quantitative. The subjects in this study were consumers of Cafe D'nada Bangkalan with a sample of 97 respondents, then the data collection tool in this study was a questionnaire. The results of this study indicate that there is an influence between sales promotion and service quality on repurchase intention at Cafe D'nada Bangkalan, partially or simultaneously. The result of the coefficient of determination is 0.517, which means 51.7% repurchasing interest at Cafe D'nada Bangkalan is influenced by the Sales Promotion (X1) and Service Quality (X2) variables. While the other 48.3% is influenced by other variables not examined in this study